Turkey - Kazakhstan Commercial Relations (1992-2014) - (:unkn) unknown (MARMARA UNIV, 2017)
In this study, commercial relations between Turkey and Kazakhstan covering the years 1992-2014 are discussed. The relationship began in 1992, because Kazakhstan declared independence at the end of 1991 and diplomatic and commercial relations with Kazakhstan started since 1992. Trade relations between the two countries in this period of 23 years were investigated for in some products. It is tried to put forth that as the years, which products shaped the trade and what products have been the subject of trade at which intensity.
Keywords: Commercial relations; importation; exportation